2011
DOI: 10.1111/j.1745-4514.2011.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Naringenin (Citrus Flavanone) on Lipid Profile in Ethanol-Induced Toxicity in Rats

Abstract: Our aim was to investigate the effect of naringenin on hyperlipidemia induced by ethanol. Groups 1 and 2 rats received isocaloric glucose and 0.5% carboxymethyl cellulose (CMC); groups 3 and 4 received 20% (6 g/kg body weight p.o.) ethanol everyday for 60 days. Groups 2 and 4 rats received naringenin (50 mg/kg body weight/day in 0.5% CMC) everyday during the last 30 days of the experiment. There were increased levels of plasma total cholesterol (TC), triglycerides (TG), free fatty acids (FFA), very low density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Naringenin is a phenolic compound belonging to the flavanone class, and its three‐ring structure effects a low water solubility . Although naringenin has been shown to display anti‐cancer, anti‐inflammatory, and anti‐microbial activities, the low water solubility limits its pharmaceutical application. The solubility of naringenin was improved 365‐ and 400‐fold when complexed dimethyl β‐cyclodextrin (β‐CD) and hydroxypropyl‐β‐CD, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin is a phenolic compound belonging to the flavanone class, and its three‐ring structure effects a low water solubility . Although naringenin has been shown to display anti‐cancer, anti‐inflammatory, and anti‐microbial activities, the low water solubility limits its pharmaceutical application. The solubility of naringenin was improved 365‐ and 400‐fold when complexed dimethyl β‐cyclodextrin (β‐CD) and hydroxypropyl‐β‐CD, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these flavanones have been reported to increase HDL cholesterol concentrations in some (104,105) but not all (106, 107) animal studies. However, little research has been done to evaluate the effect of dietary flavanones on HDL function.…”
Section: Flavanonesmentioning
confidence: 99%
“…Increases in plasma and tissue cholesterol levels of ethanol-fed rats have been attributed to upregulation of HMG CoA reductase, the ratelimiting enzyme in the biosynthetic pathway of cholesterol [23]. Studies have demonstrated the inhibitory effect of NGM (50mg/kg) administered along with ethanol, on the activity of HMG CoA reductase [24].…”
Section: Discussionmentioning
confidence: 99%